2022
DOI: 10.1039/d2ra00622g
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial roles of the AhR ligand FICZ on the regenerative potentials of BMSCs and primed cartilage templates

Abstract: FICZ/AhR axis might be a potential target to achieve optimal bone regeneration for both BMSCs and primed cartilage templates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Moreover, in vivo administration of FICZ increased bone formation rate and mineral apposition rate in WT mice (Yoshikawa et al 2021). Similarly, a recent report by Huang et al demonstrated that FICZ treatment promoted osteogenic differentiation of rat bone marrow stromal cells (Huang et al 2022). However, kynurenine (another endogenous AhR ligand) inhibited differentiation of BMSC-derived osteoblasts, reducing mineralized matrix production by these cells, and also decreased dynamic indices of bone mineralization activity (Refaey et al 2017).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 72%
See 3 more Smart Citations
“…Moreover, in vivo administration of FICZ increased bone formation rate and mineral apposition rate in WT mice (Yoshikawa et al 2021). Similarly, a recent report by Huang et al demonstrated that FICZ treatment promoted osteogenic differentiation of rat bone marrow stromal cells (Huang et al 2022). However, kynurenine (another endogenous AhR ligand) inhibited differentiation of BMSC-derived osteoblasts, reducing mineralized matrix production by these cells, and also decreased dynamic indices of bone mineralization activity (Refaey et al 2017).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 72%
“…MSCs constitute a heterogenous population of cells that can differentiate into several mesodermal cell lineages such as chondrocytes, adipocytes, and osteoblasts (Abney & Galipeau 2021). The AhR is strongly expressed in MSCs (Huang et al 2022), and many independent reports indicate that AhR-mediated signaling inhibits MSC proliferation (Zhou et al 2017, Jia et al 2021, Huang et al 2022. Human bone marrow MSC proliferation was inhibited by AhR ligand kynurenine and stimulated by AhR inhibitor SR1 in a concentration and time-dependent manner (Jia et al 2021); proliferation was also stimulated through siRNA-mediated knockdown of AhR expression, which protected against the inhibitory effects of kynurenine (Jia et al 2021).…”
Section: Role Of Ahr In Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidoreduction state is associated with bone remodeling and contributes to bone loss (e.g., osteoblasts apoptosis, osteoclast formation, and inhibits mineralization and osteogenesis) 17 . A recent study demonstrated that Cyp1a1 is involved in the regulation of the osteogenic metabolism of BMSCs 18 . Therefore, we investigated the effect of hypoxia on Cyp1a1 and the mechanism of hypoxia regulating BMSCs osteogenesis through Cyp1a1.…”
Section: Discussionmentioning
confidence: 96%